Analisis Pengetahuan Dan Minat Masyarakat Terhadap Produk Perbankan Syariah Di Kelurahaan Helvetia - Saputri, Indah; Farhani, Putri; Chairina, Chairina (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
Islamic banking is one of the economic sectors that is affected by the current economic climate. To contribute to overall economic growth, this measure becomes a benchmark for banks and other financial institutions. The people of the Helvetia village are starting to consider using Islamic banks as a transaction tool and also making Islamic banks a place to save money. The increasing interest of the Helvetia sub-district community has made Islamic banks increasingly popular among the public and used more in non-cash transactions every day. Banks that carry out business activities based on sharia or Islamic legal principles in accordance with Law No. 21 of 2008 concerning sharia banking. There is also the purpose of this study to find out about the interest and knowledge of the Helvetia sub-district community about Islamic banking which is increasing very rapidly.